Immediate salbutamol responsiveness does not predict long-term benefits of indacaterol in patients with chronic obstructive pulmonary disease - Burgel, Pierre-Régis (BMC Pulm Med, 2017)
BACKGROUND: The purpose of this study was to evaluate the correlation between immediate responsiveness with the short-acting β(2)-agonist salbutamol and effects of treatment with the ultra-long-acting β(2)-agonist indacaterol in patients with chronic obstructive pulmonary disease (COPD). METHODS: The REVERBREZ study was a phase IV, multicentre, open-label study in which patients with moderate-to-severe COPD received indacaterol 150 μg once-daily for 5 months. The primary endpoint was the correlation between immediate response of forced expiratory volume in 1 s (FEV(1)) post-inhalation of salbutamol (400 μg) at study entry and the change from baseline in trough FEV(1) after 1 month of indacaterol. Secondary endpoints included dyspnoea measured by the modified Medical Research Council (mMRC) grade and health-related quality of life measured by the clinical COPD questionnaire (CCQ). RESULTS: Of the 602 patients enrolled from 177 centres in France, 543 patients received at least one indacaterol dose, 512 patients completed 1 month of indacaterol treatment (primary endpoint), and 400 patients completed 5 months of treatment. At study entry, mean FEV(1) values before and after salbutamol inhalation were 1.54 ± 0.50 L and 1.65 ± 0.53 L, respectively. Based on the magnitude of an immediate response of FEV(1) after salbutamol inhalation at study entry, patients were classified into reversible (Rv, ≥12% and ≥200 mL from pre-salbutamol value; n = 106) and non-reversible (NRv, <12% or <200 mL from pre-salbutamol value; n = 431) groups. After 1 month of indacaterol treatment, mean absolute and relative difference in trough FEV(1) were 100 mL and 9%, respectively. No significant correlation was found between the immediate FEV(1) response to salbutamol at study entry and change from baseline in trough FEV(1) after 1 month of indacaterol treatment (correlation coefficient = 0.056 [95% CI;−0.032, 0.144] for absolute response and 0.028 [95% CI;−0.06, 0.116] for relative response). At all subsequent visits, mMRC and CCQ scores, and FEV(1) improved from baseline with no significant difference between the Rv and NRv groups. CONCLUSIONS: Immediate FEV(1) response to salbutamol did not predict the long-term benefits observed with indacaterol treatment in patients with COPD. Patients considered reversible or non-reversible to salbutamol showed comparable improvements in lung function, dyspnoea and health-related quality of life. TRIAL REGISTRATION: ClinicalTrials.gov: NCT01272362. Date: January 5, 2011